The Effect of Profitability, Liquidity on Capital Structure with Profit Growth as Moderating Variable - Dhiftania Luthfiya Azra; Yenni Samri Julianti Nasution; Nur Fadhilah Ahmad Hasibuan (Journal La Bisecoman, 2024)
This study aims to determine the effect of profitability and liquidity on capital structure with profit growth as a moderation variable in PT Perkebunan Nusantara IV Medan for the 2018-2022 period. This study uses descriptive quantitative analysis, where data is obtained through secondary data in the published annual financial statements. This study used descriptive data analysis, normality test, multicoclarity test, auotocorrelation test, heteroscedasticity test, two regression analysis tests, namely multiple linear regression analysis and moderation regression analysis, significance test t, significance test f, and dermenation coefficient test, using SPSS software version 25. The results of the study show that Profitability does not have a significant effect on Capital Structure with a significance value of 0.078 > 0.05, Liquidity has a significant effect on Capital Structure with a significance value of 0.015 < 0.05, Profit Growth is not able to moderate the effect of the Profitability variable on Capital Structure or can be said not to have a significant effect with a significance value of 0.525 > 0.05, Profit Growth unable to moderate the effect of the Liquidity variable on Capital Structure or can be said to have no significant effect with a significance value of 0.194 > 0.05. And the dependent variable of capital structure is jointly affected by the independent variables of profitability, liquidity, and the variable moderation of profit growth with significance values are 0.026 < 0.05.